Geographical influence on Tsunami Predictions in Pandeglang Regency, West Java, Indonesia - Lestari, Della Ayu; Fitriasari, Novi Sofia; Ahmad, Taufiq Ejaz; Rais, Amien; Azhari, Dhea Rahma (Forum Geografi, 2021)
Pandeglang Regency is an area that has a large potential level of Tsunamis. This is based on the fact that Geographically Pandeglang Regency located near the Krakatau Anak Volcano and plate subduction path of Indo-Australia in the Sunda Strait cause Pandeglang Regency to become one of the regions that has a tsunami potential. Therefore, it is necessary to mitigate from an early age in order to overcome and prevent large losses. One of the steps that can be taken is to identify the potential coverage area of the inundation. The results of the calculations from these data are then entered into the Tsunami scenario modeling. Which in this case is divided into 3 scenarios, for Pandeglang Regency, the first scenario with a 100-year period the maximum tsunami height from the coastline is 7.5 meters. For the second scenario with a 2000-year period with a predicted maximum height of 15 meters and the last scenario with a period of 2500 years with a predicted height of 20 meters. The results show that in the Tsunami wave modeling 7.5 m of the widest inundation occurs in Panimbang District this is due to land cover consisting of ponds, rice fields, irrigation, plantations and gentle slopes. The conditions that occur in the well-sphere cause this area to become a flooded area with the highest area at the tsunami wave modeling of 15 m. Sumur Sub-district is also the area with the largest inundation at the 20 m tsunami wave modeling.